Nursing microtheory in the prevention of delirium in older adult in the intensive care unit (Revista Latino-Americana de Enfermagem, 2023)
Objective: to describe a microtheory for nursing care in the prevention of delirium in older adult in the intensive care unit. Method: prescriptive theoretical research, based on substruction. Roy’s Adaptation Model constructs were deduced and data from the phenomenon of nursing care in the prevention of delirium in older adult in intensive care were induced, based on an integrative literature review. Results: the microtheory has a theoretical and operational system and a model of care. In the theoretical system, Roy’s focal and contextual stimulus constructs were used. From them, the concepts of focal and contextual care and the variable adaptive response to prevention were elaborated. From the relational statements, four axioms, two postulates, eight propositions and an epistemic assumption were elaborated. Two empirical indicators were established in the operating system: the Confusion Assessment Method for Intensive Care Units and the demographic/clinical history of the older adult. Subsequently, two transformational statements, four hypotheses and the model of care represented in figure were produced. Conclusion: the microtheory produced prescribes care in the prevention of delirium in older adult in intensive care, through a construct of interest to nursing, and allows interceptions for the development of instruments that guide nursing activities.